Microdialysis Techniques in Neuroscience - Di Giovanni, Giuseppe; Di Matteo, Vincenzo; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
Since its first application, microdialysis has become incredibly popular to study brain function and has been applied with success in different fields from psychopharmacology, neurobiology, and physiology in animals and also humans. Microdialysis Techniques in Neuroscience focuses on the practical aspects of microdialysis in animal and human, highlighting current technical limitations and providing a vision of what is yet to come for the determination of the most disparate compounds in the brain. The book’s contents range from new techniques for detection and quantifying the release of several different neurotransmitters in vitro and in vivo, even in freely moving animals, to sophisticated use of reverse dialysis and the application of microdialysis in pharmacokinetic studies. Each of the sixteen chapters, in fitting with the spirit of the Neuromethods series, contain an introduction that gives a broad overview of a focused topic, followed by an extensive protocol on how the experiments are performed along with invaluable practical advice.   Detailed and authoritative, Microdialysis Techniques in Neuroscience will be a valuable reference for students, neuroscientists, and physicians for the use of microdialysis in the study of brain functions and its clinical applications.
Cerebral Microdialysis: Research Technique or Clinical Tool? -- In Vivo Microdialysis to Study Striatal Dopaminergic Neurodegeneration -- Application of Reverse Microdialysis in Neuropharmacological Studies -- Microdialysis and Advances for Sampling Synaptic and Extrasynaptic Pools -- In Vivo Microdialysis for Measurement of Oxidative Metabolism in the Living Brain -- Quantitative In Vivo Microdialysis in Pharmacokinetic Studies -- Combination of In Vivo Microdialysis with Selective Electrochemical Detection for Online Continuously Monitoring Brain Chemistry -- Application of Spinal Microdialysis in Freely Moving Rats -- Monitoring Extracellular Monoamines with In Vivo Microdialysis in Awake Rats: A Practical Approach -- Intracerebral Human Microdialysis in Parkinson’s Disease -- Monitoring Extracellular Amino Acid Neurotransmitters and hROS by In Vivo Microdialysis in Rats: A Practical Approach -- Measurement of Neuropeptides in Dialysate by LC-MS -- Achieving High Temporal Resolution for In Vivo Measurements by Microdialysis -- Indirect Analysis of Nitric Oxide and Quantitation of Selective Nitric Oxide Synthase Inhibitors in Microdialysate Samples -- Determination of Histamine in Microdialysis Samples from the Rodent Brain by Column Liquid Chromatography -- Intracerebral Microdialysis in the Study of Limbic Seizure Mechanisms and Antiepileptic Drug Action Using Freely Moving Rats.
Keywords: Neurosciences; Neurobiology; Neurosciences; Neurobiology